An Economist’s Manifesto on Unemployment in the European Union - Modigliani, Franco; Fitoussi, Jean Paul; Moro, Beniamino; Snower, Denis; Solo, Robert; Steinherr, Alfred; Labini, Paolo Sylos (Journal of Income Distribution®, 1999)
This manifesto challenges a pernicious orthodoxy that has gripped Europe’s policy makers. It is that demand and supply side policies must have different aims, that a limited number of supply side policies are to be devoted to fighting unemployment, and that demand management (and particularly monetary policy) is to be devoted solely to fighting inflation. We are confident that if out proposals are given proper attention by governments and monetary authorities, unemployment can be reduced significantly in a matter of a few years. {Copyright 2000 Elsevier Science Inc. All rights reserved}